Strand 4: Connecting Individuals and Companies in a Lifelong Learning Network: Piloting the University for Industry - Milner, Helen; Thorne, Mike; Hillman, Josh (Proceedings of the International Conference on Networked Learning, 1998)
The University for Industry is a key plank of UK government education policy. Following the announcement of the concept by (then MPs, now ministers) Brown and Blunkett in 1995, the Institute for Public Policy Research (IPPR) conducted a large consultation exercise with leaders in industry and academia which led to the report "The University for Industry: creating a National Learning Network" (IPPR, 1996) detailing the University for Industry concept. Shortly after the report emerged, because of several key ideas included in the report which had originated from successful innovation from the University of Sunderland, IPPR and the University of Sunderland agreed to lead a consortium to pilot many of the ideas in the report. This paper will report on progress to date of this original pilot which is to be evaluated by the UK Department for Education and Employment but which is otherwise independent of direct government funding thanks to a public-private partnership.